Death in the castle : a novel - Buck, Pearl S. (Pearl Sydenstricker), 1892-1973 (Open Road Integrated Media, 2013)
Sir Richard and Lady Mary need to sell their family estate, a thousand year old castle. John Blayne, an American, wishes to buy the castle, take it apart piece by piece and make it into a museum in Connecticut. The castle harbors spirits of past ages, and guilty secrets of centuries past.